Surveillance of Antimalarial Drug-Resistance Genes in Imported Plasmodium falciparum Isolates From Nigeria in Henan, China, 2012–2019 - Zhao, Dongyang; Zhang, Hongwei; Ji, Penghui; Li, Suhua; Yang, Chengyun; Liu, Ying; Qian, Dan; Deng, Yan; Wang, Hao; Lu, Deling; Zhou, Ruimin; Zhao, Yuling (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria is still one of the major public problems in Nigeria, and Nigeria is one of the main source countries of the imported malaria in China. Antimalarial drug resistance is a big obstacle to the control and prevention of malaria globally. The molecular marker associated with the antimalarial drugs resistance can provide an early warning about the emergence of the resistance. The mutant prevalence of antimalarial drug-resistance genes including PfK13, Pfcrt, Pfmdr1, Pfdhfr and Pfdhps were evaluated among the imported Plasmodium falciparum isolates from Nigeria in Henan, China, from 2012 to 2019. Among the 167 imported P. falciparum isolates, the wild-type frequency of PfK13, Pfcrt, Pfmdr1, Pfdhfr and Pfdhps gene was 98.7%, 63.9%, 34.8%, 3.1% and 3.1%, respectively. The mutation of PfK13 was rare, just two nonsynonymous (S693F and Q613H) and two synonymous mutations (C469C and G496G) were identified from 4 isolates. The mutant prevalence of Pfcrt at codon 74-76 was all reduced yearly. And the prevalence of pfmdr1 86Y also decreased greatly with time. The mutant prevalence of Pfdhfr and Pfdhps was high. Meanwhile, the combined mutations of Pfdhfr and Pfdhps showed that the quadruple mutant I51R59N108-G437 (39.0%) was very common, following by the octal mutant I51R59N108-V431A436G437G581S613 (17.0%). The molecular findings updated the data about the antimalarial drug-resistance genes and provided the supplemental information for Nigeria.